Doctoral students' conceptions of online teaching portfolios. An exploration of the authenticity and performativity spectrum - Helga Dorner; Joanna Renc-Roe (Forum Neue Medien in der Lehre Austria, 2016)
This paper outlines findings from a research project on the reflective processes involved in the creation of online teaching portfolios by doctoral students of an international, graduate university in Europe. The study was conducted to identify conceptions of online teaching portfolios and to explore how these conceptions relate to notions of academic professionalism. Fifteen doctoral students who took part in an academic development programme were interviewed. The semi-structured interviews were analysed qualitatively using a grounded theory approach. Students were found to oscillate between performative and authentic repertoires of reflective work. Their conceptions were also found to reflect notions of academic professionalism, along a spectrum from instrumentalist-performative to reflective-authentic notions. 30.09.2016 | Helga Dorner & Joanna Renc-Roe